Report of the Committee on Establishment of an Accounting Commission. - Bedford, Norton M.; Hendriksen, Eldon S.; Keller, Thomas F.; Nelson, Carl L.; Rappaport, Alfred; Solomons, David; Sorter, George H. (The Accounting Review, 1971)
Abstract The article focuses on a report of the Committee on Establishment of an Accounting Commission. The charge to this committee, as formulated by the American Accounting Association Executive Committee at its August 1970 meeting, is to consider the feasibility and desirability of establishing a Commission to study and recommend an organizational structure for advancing the formulation and modification of generally accepted accounting principles and the issuance of authoritative pronouncements concerning the application of such principles. If the committee recommends that such a Commission should be formed, the committee also should recommend the objectives, method of selecting members, and means of financing the work of the Commission. At the present time, accounting principles are formulated largely by the Accounting Principles Board. Inevitably, therefore, any dissatisfaction with methods of formulating principles is tantamount to dissatisfaction with the Board. High on its agenda for 1971 are other problems which currently obscure the effective disclosure of financial performance, such as the treatment of inter-corporate investments, financial reporting by diversified companies and others.